Problems with radical corrective surgery after ascending aorta to right pulmonary artery shunt (Waterston's anastomosis) for cyanotic congenital heart disease. Issue 11 (November 1975) - Somerville, J; Barbosa, R; Ross, D; Olsen, E
Abstract : Forty-five patients with Fallot's tetralogy or pulmonary atresia had total correction 2 to 6 years after palliative ascending aorta to right pulmonary artery anastomosis (Waterston's shunt). The operative mortality for total correction is increased in this group. Patients shown subsequently to have had a good anatomical correction died unexpectedly with high central pulmonary artery pressure, falling arterial PO2, low cardiac output, and progressive acidosis. The cause of this syndrome was difficult to determine. Histological examination of the lungs showed that severe pulmonary arteriolar thickening was not present. The factors apparently predisposing to these postoperative difficulties were kinking of the right pulmonary artery and/or lone perfusion of the right lung, remaining uncorrected for several years, in patients with pulmonary atresia or with Fallot's tetralogy with a shunt performed under the age of 3 years. In survivors, stenosis of the right pulmonary artery frequently occurred but was rarely severe. In view of these difficulties, early haemodynamic and angiocardiographic assessment is recommended in all patients with aorta to right pulmonary artery anastomosis, irrespective of the clinical result, in order to delineate the central pulmonary artery anatomy and assess perfusion of each lung; if kinking of the right pulmonary artery and inadequate perfusion of the central pulmonary arteries and left lung are demonstrated, early radical corrective surgery is recommended.